A muse of fire: why the U.S. Military forgets what it learns in war - Askonas, J (2019)
Wars are expensive and relatively rare, and so states have strong incentives to learn from war and improve their military performance over time. And yet, even in highly capable great power militaries, the lessons of previous wars are routinely lost. Why do militaries forget what they learn in war? Examining evidence from two cases across the American experiences in Vietnam and Iraq, I find that the strongest causal evidence for why the US military forgets what it learns in war is in organizational selection. The demobilization and post-war retooling process destroys the specific sub-organizations which learn in war, namely joint task forces and ad hoc task-built organizations. This research has the potential to make a significant and novel contribution both to our understanding of repeated American foreign policy mistakes and to the broader literature on military adaptation and effectiveness.